BAHASA KIAS PADA IKLAN TV - Desak Putu Eka Pratiwi, (SPHOTA: Jurnal Linguistik dan Sastra, 2016)
ABSTRACT Language of advertisement is a very unique and controversial. Attracting attention, increasing imagination, and simplifying memories are the main functions of language of advertisement. So the use of figurative language is very common in advertisements. Figurative language tries to create particular effects by violating or exploiting language rules. Advertisers love using figurative language because the image of the product can be built up through the use of irrational language. This research aims at analyzing types and meaning of figurative language used in TV commercial advertisements. There are seven advertisements used as data source, such as the advertisement of Kopi Kapal Api, Energen Sereal, Wafer Tango, Kecap Bango, Teh Botol Sosro, Fruitea, dan Ades. The data were collected through observation and note taking method. The data were then analyzed using the theory of figurative language proposed by Keraf (2006). The analyzed data were presented in informal method. Keywords: advertisement, figurative language, meaning